Hepatic Angiosarcoma Masquerading as Hemangioma: A Challenging Differential Diagnosis - Garcia, Ana Rita (2017)
Hemangiomas are usually diagnosed based on ultrasound findings. The presence of symptoms, rapid growth or atipical imagiological findings should make us consider other diagnoses, including malignant tumors such as angiosarcomas. We describe the case of a previously healthy 46-year-old female without a history of exposure to carcinogens who presented with abdominal pain for two months. Diagnostic work-up revealed elevated gamma-glutamyl transferase and lactate dehydrogenase levels. Abdominal ultrasound described a large nodular lesion in the right lobe of the liver described as a hemangioma. One month later, a computed tomography-scan was made and revealed the same lesion, which had grown from 13.5 to 20 cm, maintaining typical imaging characteristics of a hemangioma. A right hepatectomy was performed and pathology revealed an angiosarcoma. After surgery, a positron emission tomography-computed tomography scan showed hepatic and bone metastasis. The patient started taxane-based chemotherapy and lumbar palliative radiotherapy, but died 10 months after surgery. This case shows how difficult it is to diagnose hepatic angiosarcoma relying only on imaging findings. Two abdominal computed tomography -scans were performed and none suggested this diagnosis. Angiosarcoma is a very aggressive tumour with an adverse prognosis. Surgery is the only curative treatment available. However, it is rarely feasible due to unresectable disease or distant metastasis.